Sustainable residential low density urban development: integrating sustainable consciousness with commercial viability - Jahn Kassim, Puteri Shireen; Ali, Maisarah; A. Haron, Husam; M. L. Tan, Rosemary (2008)
This paper will discuss the present integration of sustainable features in a self-contained residential development in the growing urban density in Malaysia - consisting of 36 units semi-detached and 4 units terrace houses – within the constraints of commercial viability of such a project. The projects features the layout planning for green-shared landscaped courtyard area, a rainwater harvesting system links all units for landscaping needs, double brick walls for energy efficiency, heat reclaim system for hot water and roof insulation for heat gain reduction. Each unit features a four-storey structure with a double frontage design, foyer space in the 1st level. Dining, kitchen and living on the 2nd level. Bedrooms and a family room on the 3rd and 4th level. The focus includes the outcome of an evaluation of the energy efficiency impact of the double cavity external wall and a heat reclaim system used in each unit in the development - where air conditioning heat is reclaimed at night for hot water use in the morning. A solar shadowing impact of two adjacent developments consisting of high-rise condominiums on the entire developments for different times of the day were also done to ascertain roof surfaces which can be used for grid connected solar panels. The paper presents an attempt by an ecological conscious developer to integrate green features – including rainwater harvesting and communal strategies such as shared green space within the commercial and resource constraints of a project.